Lectotypification in Zeuxine Lindl. (Orchidaceae) - Avishek Bhattacharjee (Taiwania, 2011)
Lectotypification of Psychechilos gracile Breda [≡ Zeuxine gracilis (Breda) Blume], Zeuxine pulchra King & Pantl. and Zeuxine reflexa King & Pantl. are provided in the present paper along with the photographs of selected lectotypes.